Bird communities in African cocoa agroforestry are diverse but lack specialized insectivores. Issue 6 (14th March 2021) - Jarrett, Crinan; Smith, Thomas B.; Claire, Tabe T. R.; Ferreira, Diogo F.; Tchoumbou, Melanie; Elikwo, Malange N. F.; Wolfe, Jared; Brzeski, Kristin; Welch, Andreanna J.; Hanna, Rachid; Powell, Luke L.
Abstract: Forests are being converted to agriculture throughout the Afrotropics, driving declines in sensitive rainforest taxa such as understorey birds. The ongoing expansion of cocoa agriculture, a common small‐scale farming commodity, has contributed to the loss of 80% rainforest cover in some African countries. African cocoa farms may provide habitat for biodiversity, yet little is known about their suitability for vertebrate fauna, or the effect of farm management on animal communities. Here, we report the first in‐depth investigation into avian diversity and community composition in African cocoa, by assembling a dataset of 9, 566 individual birds caught across 83 sites over 30 years in Southern Cameroon. We compared bird diversity in mature forest and cocoa using measures of alpha, beta and gamma diversity, and we investigated the effect of cocoa farm shade and forest cover on bird communities. Gamma diversity was higher in cocoa than forest, though alpha diversity was similar, indicating a higher dissimilarity (beta diversity) between cocoa farms. Cocoa farms differed from forest in community composition, with a distinctive decrease in relative abundance of insectivores, forest specialists and ant‐followers and an increase in frugivores. Within cocoa farms, we found that farms with high shade cover in forested landscapes resulted in higher relative abundance and richness of sensitive forest species; shady farms contained up to five times the proportion of forest specialists than sunny farms. Synthesis and applications . Sunny African cocoa farms were less able to support sensitive bird guilds compared with shaded farms in forested landscapes. Our findings support the notion that certain ecological and dietary guilds, such as ant‐followers and forest specialists are disproportionately affected by land‐use change. In light of the current push to increase cocoa production in sub‐Saharan Africa, our results provide policymakers opportunities for more wildlife‐friendly cocoa schemes that maximize avian diversity. Abstract : Sunny African cocoa farms were less able to support sensitive bird guilds compared with shaded farms in forested landscapes. Our findings support the notion that certain ecological and dietary guilds, such as ant‐followers and forest specialists are disproportionately affected by land‐use change. In light of the current push to increase cocoa production in sub‐Saharan Africa, our results provide policymakers opportunities for more wildlife‐friendly cocoa schemes that maximize avian diversity.